Cell and tissue culture: research and technology from Islamic perspective - Abdull Rasad, Mohammad Syaiful Bahari (IIUM Press, 2013)
This book is an attempt to capture the principles of human or animal cell culture and issues from Islamic perspective. there are many achievements which were made possible through the development and advancement of science and technology in the area of cell and tissue culture. Nowadays, the technologies available to mankind are far more sophisticated and advanced. Most assuredly, these technologies have, and will make, a great impact on the life of mankind and their wellbeing. Consequently, for Muslims, the concern lies not on the advancement, but on whether the laws and regulations of Islam are wisely and properly inculcated into these progressions of science and technology so that they are parallel to the will and wishes of Allah swt. Considering the breadth of topics covered, the book will be essential reading for the novice and expert alike in various fields and will serve as a valuable reference resource for students and researchers. It provides, from experts in the field, the basis and application of animal cell culture technology, including the use of the cells in recent research as well as Islamic perspective. In essence, this book discusses various dimensions of cell culture in relation to research. This is perhaps the first book of its kind which links one of the purposes of Islamic perspective to research and technology of cell culture.